2022
DOI: 10.1039/d2cc01744j
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon fluorescence imaging of the cerebral peroxynitrite stress in Alzheimer's disease

Abstract: Cerebral oxidative stress, especially peroxynitrite (ONOO−) in brains is suggested to play an underlying role in Alzheimer’s disease (AD) pathology. However, limited by the optical penetration depth and poor blood-brain...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The final product 5a was purified using chromatography with CH 2 Cl 2 /MeOH (100 : 1, v/v) as a purple black solid (103. 4…”
Section: Materials and Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The final product 5a was purified using chromatography with CH 2 Cl 2 /MeOH (100 : 1, v/v) as a purple black solid (103. 4…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…1,2 With the development of fluorescent probes, researchers have continued to improve the probe structure, and a series of new fluorescent probes with excellent performance have been developed and explored. 3,4 Nitrogen-containing heterocyclic compounds, which are widely present in nature, are one of the basic units with biological activity. 5,6 With this variety of advantages, they have been widely introduced into the construction of fluorescent probe structures, and also widely used in fluorescent labelling and biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…The overproduction of ONOO − is suggested to be one of the predominant executioner of regulated cell death. Tang's group [68] develop a two−photon fluorescence probe NATP (Figure 12) for ONOO − and applied it to study the connections between ONOO − overproduction and ferroptosis of neuronal cells. NATP was designed by functionalizing naphthalimide fluorophore with a oxindole as recognition site for ONOO − .…”
Section: Probe For Onoo −mentioning
confidence: 99%
“…Ferroptosis is a new non-apoptotic cell death pathway that is characterized by excessive accumulation of iron-dependent lipid peroxides . Recent studies have found that ferroptosis is also accompanied by the upgeneration of ROS levels and changes in viscosity or polarity. On the other hand, mounting research indicated that the pathophysiological microenvironments, such as increased viscosity and decreased polarity, have been regarded as effective markers of tumors. ,, Meanwhile, recent studies have also shown that a significant increase in the ONOO – level is observed during tumor progression, suggesting its potential as a tumor marker. , However, owing to the lack of a suitable probe, the simultaneous visualization of ONOO – , viscosity, and polarity in ferroptosis and cancer models has not been validated.…”
mentioning
confidence: 99%